The development of PBL-based science module to improve students’ creative thinking skill in MTsN Subang anak - Jasmaini Jasmaini; Festiyed Festiyed; Djusmaini Djamas (Fakultas Ilmu Pendidikan UNP)
The purpose of this study was to produce module based on PBL to improve creative thinking skills which are valid, practical and effective to use in learning science. The design of this study is research and development by using 4-D model which consists of Four phase. The results of development phase, showed that module based on PBL model to improve the creative thinking skills of learners is valid by mean of (0,88), For the practicality, the mean of questionnaire responses learners towards the product was 87.20, categorized as very practical; the mean of questionnaire responses of teachers was 92.75, also categorized as very practical. The result of the develop phase showed that the product met the criteria of effectiveness as the data obtained showed that there was improvement of learners competences: cognitive, affective, psychomotor, as well as creative thinking skills. The mean value of cognitive competence was 84.00; affective competence was 84.65; and psychomotor competence was 82.73. Mean while, the mean value of creative thinking skills improvement was average and low in every meeting.